Complications Among Adults Hospitalized With Influenza: A Comparison of Seasonal Influenza and the 2009 H1N1 Pandemic. (9th April 2014) - Reed, Carrie; Chaves, Sandra S.; Perez, Alejandro; D'Mello, Tiffany; Daily Kirley, Pamala; Aragon, Deborah; Meek, James I.; Farley, Monica M.; Ryan, Patricia; Lynfield, Ruth; Morin, Craig A.; Hancock, Emily B.; et al.
Abstract : Adults hospitalized with 2009 pandemic influenza were younger than those hospitalized in previous influenza seasons and more likely to have lower respiratory tract complications and corresponding indicators of severe illness including intensive care admission, mechanical ventilation, or death. Abstract : Background. Persons with influenza can develop complications that result in hospitalization and death. These are most commonly respiratory related, but cardiovascular or neurologic complications or exacerbations of underlying chronic medical conditions may also occur. Patterns of complications observed during pandemics may differ from typical influenza seasons, and characterizing variations in influenza-related complications can provide a better understanding of the impact of pandemics and guide appropriate clinical management and planning for the future. Methods. Using a population-based surveillance system, we compared clinical complications using International Classification of Diseases, Ninth Revision ( ICD-9 ) discharge diagnosis codes in adults hospitalized with seasonal influenza (n = 5270) or 2009 pandemic influenza A(H1N1) (H1N1pdm09; n = 4962). Results. Adults hospitalized with H1N1pdm09 were younger (median age, 47 years) than those with seasonal influenza (median age, 68 years; P < .01), and differed in the frequency of certain underlying medical conditions. Whereas there was similar risk for many influenza-associated complications, after controlling for age and type of underlying medical condition, adults hospitalized with H1N1pdm09 were more likely to have lower respiratory tract complications, shock/sepsis, and organ failure than those with seasonal influenza. They were also more likely to be admitted to the intensive care unit, require mechanical ventilation, or die. Young adults, in particular, had 2–4 times the risk of severe outcomes from H1N1pdm09 than persons of the same ages with seasonal influenza. Conclusions. Although H1N1pdm09 was thought of as a relatively mild pandemic, these data highlight the impact of the 2009 pandemic on the risk of severe influenza, especially among younger adults, and the impact this virus may continue to have.